Exploring language in schizophrenia: The use of low frequency words as a linguistic marker schizophrenia symptoms - Martínez-Cano, Alfonso; Santos, José Luis; Martínez-Lorca, Manuela; Polonio-López, Begoña (Revista de Investigación en Logopedia, 2026)
Our study aims to assess lexical uniqueness in Spanish-speaking individuals with schizophrenia, as well as analyze the peculiarity in word usage concerning symptom predominance. Furthermore, we aim to investigate whether word associations could elucidate the usage of uncommon terms by this population. The sample consists of 50 people diagnosed with schizophrenia (56% with a predominance of positive symptoms and 44% with negative symptoms). The semantic and phonological verbal fluency test was administered. Through the ESPAL database, the frequencies of the generated words were analyzed. Just as the associations of the words were studied through an analysis of blinded judges. People with schizophrenia use a greater number of low-frequency words, especially in positive symptoms in both phonological verbal fluency and semantic verbal fluency, the differences being statistically significant. We observed a greater association of words depending on the sound in the phonological fluency tests while in semantic fluency a greater semantic association was observed both with statistical significance. Our results support the validity of the method for assessing word distinctiveness by people with schizophrenia, especially when they present positive symptoms. The use of rare words could be used as an objective measure for the distinction of symptomatology in schizophrenia.
Keywords: Language; Low-frequency words; Negative symptomatology; Positive symptomology; Schizophrenia